Characterization of WEEE plastics and their potential valorisation through the production of 3D printing filaments. Issue 4 (August 2021) - Cafiero, L.; De Angelis, D.; Di Dio, M.; Di Lorenzo, P.; Pietrantonio, M.; Pucciarmati, S.; Terzi, R.; Tuccinardi, L.; Tuffi, R.; Ubertini, A.
Abstract: Plastic is probably the fraction of the waste of electrical and electronic equipment (WEEE) most challenging to manage and the market of recycled plastics from WEEE is limited to few cases. In this study, twenty WEEE plastic samples collected in two material recovery facilities (MRFs) from manually sorted housings and components and among some discarded devices stored in Casaccia Research Center were analysed through infrared identification and chemical-physical characterization. The analyses were carried out in order to select the suitable samples for mechanical recycling in 3D printer filaments. Eleven different polymers or blends were found in the WEEE samples and the majority of those collected in the MRFs resulted as mixtures of different plastics, although often of styrene-based nature. On the other hand, many WEEE samples showed a good similarity to the corresponding virgin polymers with a content of halogens and inorganic fillers less than 0.2 and 5 wt%, respectively. The thirteen selected WEEE plastic samples were washed, reduced to < 4 mm and extruded in filaments with the proper diameter. The polymeric heterogeneity and the presence of foreign materials in some samples were the main critical issues highlighted during the extrusion. The suitable filaments were used to print test objects with different geometries. The quality control of the scanned objects, through a structured-light 3D scanner, showed that specimens printed with WEEE plastic filaments had no significant higher deviation from the model design in comparison to the same object produced using the commercial filaments. Graphical Abstract: ga1 Highlights: Many WEEE samples were heterogeneous polymeric mixtures, mainly styrene-based. Foreign materials was the main problem during the extrusion of WEEE samples. Eight WEEE plastic samples were extruded into good or excellent filaments. Specimens printed from recycled and commercial filaments showed comparable quality. WEEE plastics can be up-cycled in 3D printing filaments.